Aid Effectiveness Reconsidered: Panel Data Evidence for the Education Sector - Katharina Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
Applying the general question of aid effectiveness to the sector of education, this paper reveals an overall positive effect of development assistance on primary enrolment. However, even the most optimistic estimates clearly show that at any realistic rate of growth, aid will never be able to move the world markedly closer towards the internationally agreed objective of education for all. Universal primary education requires increased efficiency of educational spending by donors and national governments alike. Moreover, the recipient countries' general political and institutional background matters. Under conditions of bad governance, the impact of aid on enrolment can actually turn negative.
Keywords: F35; O15; I22; 330; aid effectiveness; primary education; good governance; Entwicklungshilfe; Bildungsfinanzierung; Bildungsinvestition; Wirtschaftspolitische Wirkungsanalyse; Good Governance; ldc